1943
DOI: 10.1111/j.1365-2621.1943.tb16552.x
|View full text |Cite
|
Sign up to set email alerts
|

INFLUENCE OF COOKING PROCEDURE UPON RETENTION OF VITAMINS AND MINERALS IN VEGETABLES1

Abstract: The nev-er developments in the field of nutrition have indicated that some of the most important elements in our diets, invisible and undetectible by the senses of taste and smell, are lost during the cooking of foods. These are the vitamins and the essential minerals. Prior to these newer developments, the primary function of cooking was to prepare foods in an edible form. In order to preserve the nutritive value of foods, the cook must now look to the nutritionist to ascertain what effects the various operat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1946
1946
2015
2015

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 10 publications
1
8
0
Order By: Relevance
“…Steamed fresh samples retained the full amount of thiamine. Generally these results agree with those of Collings (1946) and Oser et al (1943) who reported 87% to 100% retention of thiamine depending on proportions of water used and cooking pressures. Since thiamine in our samples were in the lower reported ranges (under 80 pg/lOO g), it is possible that retention characteristics of this vitamin are different at the lower concentrations.…”
Section: Discussionsupporting
confidence: 94%
See 1 more Smart Citation
“…Steamed fresh samples retained the full amount of thiamine. Generally these results agree with those of Collings (1946) and Oser et al (1943) who reported 87% to 100% retention of thiamine depending on proportions of water used and cooking pressures. Since thiamine in our samples were in the lower reported ranges (under 80 pg/lOO g), it is possible that retention characteristics of this vitamin are different at the lower concentrations.…”
Section: Discussionsupporting
confidence: 94%
“…Oser et al (1943) reported a generally high retention (83%) of riboflavin by cooking. Our results showed significant losses from boiling, but full retention in steamed and microwaved fresh samples.…”
Section: Resultsmentioning
confidence: 97%
“…For all four methods summarized together the retentions in the cabbage, shredded or cut in small pieces, were one-fourth to all of the ascorbic acid ; in spinach, without stems in one study, one-fourth to threefifths of the ascorbic acid, one-half to four-fifths of the thiamin, and one-half to four-fifths of the riboflavin; in peas one-half to four-fifths of the ascorbic acid, one-half to almost all of the thiamin, and two-thirds to almost all of the riboflavin. These values were taken from reports by Halliday and Noble (1936) ; Wellington and Tressler (1938) ; Lunde, Kringstad, and Olsen (1940) ;Brinkman, Halliday, Hinman, and Hamner (1942) ;Higgins (1942) ; MacGregor (1942) ;Oser, Melnick, and Oser (1943) ;Gleim, Tressler, and Fenton (1944) ; Ireson and Eheart (1944) ; and Noble and Waddell (1945).…”
mentioning
confidence: 99%
“…Reported retentions in drained cooked broccoli range from 83% by Oser, et al (15), and from 83% to complete retention by Collings ( 5 ) depending upon the method of cooking. Collings also reported some increases of riboflavin during cooking.…”
Section: By Collings ( 5 )mentioning
confidence: 96%